The devil in the holy water or the art of slander from Louis XIV to Napoleon - Darnton, Robert 1939- (Material texts, 2010)
Interlocking libels. The armor-plated gazetteer -- The devil in the holy water -- The Parisian police unveiled -- The secret life of Pierre Manuel -- The end of the line -- Politics and police work. Slander and politics -- The book police at work -- A double agent and his authors -- Secret missions -- Hugger-mugger -- Entrapment -- The view from Versailles -- The devil in the Bastille -- Bohemians before Bohemianism -- The Grub Street route to revolution -- Slander into terror -- Words and deeds -- Postscript, 1802 -- The literature of libel : basic ingredients. The nature of libels -- Anecdotes -- Portraits -- News -- The literature of libel : private lives. Revolutionary metamorphoses -- Sex and politics -- Decadence and despotism -- Royal depravity -- Private lives and public affairs -- Conclusion